The Intercultural Accomodation Between Ethnic Arabics, Chines, and Malays in Palembang - Aflatun Muchtar; Anggi Wahyu Ari; Aristhopan Firdaus; Zakki Faddad; Eko Purnomo (Jurnal Sosiologi Agama, 2024)
This study tries to see how the forms of accommodation and interaction models between Arab, Chinese, and Malay communities are so that they live side by side in Palembang that this city gets the title of a Zero Conflict city. This study uses an ethnographic approach by recording events that affect intercultural interactions. In addition, the data collection technique was carried out by engaging the three communities, interviewing, observing, and documenting the object under study. This study concludes that the three ethnic groups live in Palembang’s same social and economic ecosystem and adapt well. However, there have been conflicts involving the Chinese community in Palembang. The interaction pattern between the three tribes is based on values ​​, which is transactional harmonious inter-ethnic integration.